The Role Of Career Decision-Making Self-Efficacy And Perceived Positive Parenting Towards Future Orientation In Boarding School Adolescents In Bandung - Yanti Rubiyanti; Hendriati Agustiani; Ahmad Gimmy Prathama Siswadi; Ratna Jatnika (CV. AFDIFAL MAJU BERKAH, 2023)
During adolescence, individuals begin to form an identity and plan for their future, including choosing a career that suits their interests and abilities. The purpose of this study was to determine the extent to which the role of career decision making, selfefficacy, and perceived positive parenting affects future orientation in boarding school adolescents in Bandung. This study uses the Cross Sectional Regression method. Data were collected through questionnaires distributed to boarding school adolescents in Bandung who were respondents in this study. The collected data will be analyzed using regression analysis techniques. The results showed that Career Decision Making, Selfefficacy, and Perceived Positive Parenting play a role in future orientation in boarding school adolescents in Bandung. The ability of adolescents to make the right career decisions and in accordance with their interests, values, and abilities will affect their future direction and goals. Adolescents with high levels of selfefficacy tend to have strong confidence in facing challenges and achieving their future goals. In addition, positive parenting, such as emotional support, open communication, and encouragement to achieve goals, can influence adolescents' attitudes and behaviors towards future orientation.